Análisis del Problema del Ruido en Sistemas TS-OCDMA Coherentes - Amaya Ocampo, Waldimar Alexander; Gómez Paredes, Juan Carlos (Ingeniería, 2006)
This paper descibes the analysis related to the noise problems that exist in the TS-OCDMA Systems (Time Spreading - Optical Code Division Multiple Access). This noise is composed by the Beat Noise, Multiple Access Interference Noise, thermal and Shot Noise of the electronics devices presents in the detection process. The model of noise in this paper is evaluated through simulations in which the main parameters to be considered are the power penalty, the BER and the crosstalk.